The thermal conductivity of polyamorphous state of solid monohydroxyl alcohols - Krivchikov, A.I.; Korolyuk, O.A.; Sharapova, I.V. (Физика низких температур, 2012)
New measurement results on the thermal conductivity of solid ethyl alcohol С₂Н₅ОН in the interval from 2 K to the melting temperature are presented. The annealing effect in the thermal conductivity of the orientationally ordered phase of the alcohol has been observed in a wide range of temperatures. This phase was obtained as a result of the irreversible first-order phase transition from an orientationally disordered crystal of cubic structure at T = 109 K. The thermal conductivity was observed to increase as the monoclinic lattice changed from a less stable phase to a more stable one. The growth may be due to the improved quality of the completely ordered crystal. A comparative analysis of the temperature dependences of thermal conductivity κ(T) was performed for solid monohydroxyl alcohols CH₃OH, С₂Н₅ОН, С₂D₅ОD, C₃H₇OH and C₄H₉OH in the disordered orientational and structural states. At low temperatures the thermal conductivity of a series of monohydroxyl structural glasses of alcohols increases with the mass of the alcohol molecule by a linear dependence.